Transforming ecological knowledge into collaborative action: Lessons of environmental communication from the Balinese Community - Assegaf Achmad Hamudi; Sarwoprasodjo Sarwititi; Kinseng Rilus; Dharmawan Arya Hadi (BIO Web of Conferences)
Environmental communication is crucial for raising awareness, instilling a sense of urgency, and encouraging participation in conservation efforts. However, scientists and policymakers often face challenges in conveying complex ecological issues clearly and effectively, particularly to the general public and indigenous communities. This study aims to analyze and derive lessons from the Tukad Bindu Community, an environmental movement led by the indigenous Balinese community in Kesiman Village, which has managed to mobilize local communities and garnered support from partner organizations to collaborate in transforming the Bindu River from being a polluted area into both a community-based ecotourism destination and a hub for environmental dialogue among stakeholders. The research utilizes qualitative analysis of interviews with community leaders and local stakeholders, framed within the participatory environmental communication (PEC) approach, to illustrate the process by which the Balinese community integrates indigenous knowledge with scientific understanding in their environmental communication strategies. The study demonstrates how integrating scientific knowledge and strategic approach to local wisdom and a participatory approach can encourage collective action and build the community's problem-solving capacity.